2020
DOI: 10.13057/biodiv/d210714
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of oral irrigation with an extract of green microalga Nannochloropsis oculata as an anti-inflammatory in rats infected with Aggregatibacter actinomycetemcomitans

Abstract: Abstract. Revianti S, Andriani D, Parisihni K, Wahjuningsih E, Widyastuti. 2020. Effectiveness of oral irrigation with an extract of green microalga Nannochloropsis oculata as an anti-inflammatory in rats infected with Aggregatibacter actinomycetemcomitans. Biodiversitas 21: 2977-2981. Aggressive periodontitis is strongly correlated with Aggregatibacter actinomycetemcomitans, a periodontopathic bacterium, which releases endotoxins and lipopolysaccharides (LPS). LPS acts as a stimulus to a variety of host cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Contrastingly, there are studies which ascribe a positive effect of N. oculata to the immune system of the host, in response to an inflammatory stimulus. Revianti et al (2020) orally administered N. oculata to rats infected with a periodontopathic bacterium to assess the anti-inflammatory activity of the microalga [70]. As expected, the study revealed a higher expression of IL-10 than that observed in the control when the animals were subjected to an inflammatory stimulus (infection), an expression which was increased when the animals were orally irrigated with a solution of the microalga (ca.…”
Section: Anti-inflammatory Activitymentioning
confidence: 69%
“…Contrastingly, there are studies which ascribe a positive effect of N. oculata to the immune system of the host, in response to an inflammatory stimulus. Revianti et al (2020) orally administered N. oculata to rats infected with a periodontopathic bacterium to assess the anti-inflammatory activity of the microalga [70]. As expected, the study revealed a higher expression of IL-10 than that observed in the control when the animals were subjected to an inflammatory stimulus (infection), an expression which was increased when the animals were orally irrigated with a solution of the microalga (ca.…”
Section: Anti-inflammatory Activitymentioning
confidence: 69%